2013
DOI: 10.12659/aot.883843
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of malignancies in cardiac allograft recipients – a single-center experience

Abstract: The risk of malignancy development is many times higher for HT patients than in the general population. The high incidence rate for pulmonary carcinoma in the analyzed group of patients was most likely related to smoking before transplantation and continuation of smoking after the procedure in the case of patients who received immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…According to current data, skin cancer is the most frequent malignancy among HTRs. A number of studies have also reported a higher incidence of other cancers, such as lymphoproliferative diseases, lung cancer or uterine and cervical dysplasia 3,4 . This study analyses the data of post-transplant malignancies among HTRs in the CzechRepublic.…”
Section: Introductionmentioning
confidence: 99%
“…According to current data, skin cancer is the most frequent malignancy among HTRs. A number of studies have also reported a higher incidence of other cancers, such as lymphoproliferative diseases, lung cancer or uterine and cervical dysplasia 3,4 . This study analyses the data of post-transplant malignancies among HTRs in the CzechRepublic.…”
Section: Introductionmentioning
confidence: 99%
“…The ISHLT 2015 registry reported malignancy developments in about 3.7% of lung transplant recipients who survive to 1 year, 16.6% within 5 years after transplantation, and in 29.1% within 10 years (4). Data on other solid organ recipients are similar (7,8).…”
Section: Discussionmentioning
confidence: 80%
“…These are important especially in patients with prior history of nicotine abuse and malignancy, and older age [19]. For aerodigestive malignities, surveillance strategies did not give result with earlier diagnosis, but in cases with higher risk rates physicians should be more suspicious [20].…”
Section: Discussionmentioning
confidence: 99%